Dynamics of the residential real estate market during the implementation of the Safe Credit 2% programme – a case study of selected cities in Poland - Adamiczka, Hanna; Pluta, Agata (Dynamika rynku nieruchomości mieszkaniowych w okresie realizacji programu Bezpieczny Kredyt 2% na przykładzie wybranych miast w Polsce, 2025)
Aim: The paper aimed to present the situation in the housing market of the seven largest cities in Poland (Warsaw, Kraków, Wrocław, Poznań, Gdańsk, Gdynia and Łódź) in the period of implementation of the Safe Credit 2% programme, with a particular emphasis on its impact on the dynamics of residential property prices. Methodology: The research employed a qualitative and quantitative approach based on reviewing the available literature on the subject and analysing statistical data. The data sources included, among others, reports from the Local Data Bank, the National Bank of Poland and AMRON-SARFiN. The authors applied a comparative approach, including a longitudinal (2010-2023) and a quarterly snapshot (Q1 to Q4 2023 compared to Q1 to Q4 q 2022) when considering the impact of the Safe Credit 2% programme. Results: The analysis showed that Safe Credit 2% had a significant impact on increasing housing affordability, however its short duration did not allow it to effectively stimulate the housing supply, resulting in a sharp increase in house prices. As a result, despite improving the housing situation for some groups in society, the overall availability of housing for those who did not meet the programme’s criteria deteriorated, such as middle-income households. Note that the increase in housing prices continued even after the programme ended, thus exacerbating the barriers in access to housing for average households. Implications and recommendations: The results indicated that an effective housing policy should simultaneously stimulate demand and supply. Due to the long-term construction process, short-term programmes such as Safe Credit 2% were insufficient to stimulate the housing supply effectively. It is recommended that long-term mechanisms and price stabilisation instruments are implemented to avoid sudden changes in the market. It is also important to conduct further research evaluating the effectiveness of the housing policies introduced. Originality/value: The article makes an important empirical contribution to analysing the impact of housing policy on housing prices and housing availability on Poland’s largest real estate markets. It provides detailed information on the effects of the Safe Credit 2% programme, which can be an important source of knowledge for researchers, policymakers and investors.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 16-33
Keywords: Safe Credit 2%; housing programme; housing policy; real estate market; housing prices; Bezpieczny Kredyt 2%; program mieszkaniowy; polityka mieszkaniowa; rynek nieruchomości; ceny mieszkań